Metabolomics and mass spectrometry imaging reveal the chronic toxicity of indoxacarb to adult zebrafish (Danio rerio) livers - Ma, Lianlian; Yin, Zhibin; Xie, Qingrong; Xu, Yizhu; Chen, Yingying; Huang, Yudi; Li, Zhen; Zhu, Xinhai; Zhao, Yuhui; Wen, Wenlin; Xu, Hanhong; Wu, Xinzhou (Journal of hazardous materials, 2023)
Indoxacarb is a widely used insecticide in the prevention and control of agricultural pests, whereas its negative effects on non-target organisms remain largely unclear. Herein, we demonstrated the integrated metabolomics and mass spectrometry imaging (MSI) methods to investigate the chronic exposure toxicity of indoxacarb at environmentally relevant concentrations in adult zebrafish (Danio rerio) liver. Results showed that movement behaviors of zebrafish can be affected and catalase (CAT), glutamic oxalacetic transaminase (GOT), and glutamic pyruvic transaminase (GPT) activities were significantly increased after indoxacarb exposure for 28 days. Pathological analysis of zebrafish livers also showed that cavitation and pathological reactions occur. Metabolomics results indicated that metabolic pathways of zebrafish liver could be significantly affected by indoxacarb, such as tricarboxylic acid (TCA) cycle and various amino acid metabolisms. MSI results revealed the spatial differentiation of crucial metabolites involved in these metabolic pathways within zebrafish liver. Taken together, these integrated MSI and metabolomics results revealed that the toxicity of indoxacarb arises from metabolic pathways disturbance, which resulted in the decrease of liver detoxification ability. These findings will promote the current understanding of pesticide risks and metabolic disorders in zebrafish liver, which provide new insights into the environmental risk assessment of insecticides on aquatic organisms. [Display omitted] •Long-term exposure of environmental levels of indoxacarb impairs zebrafish liver.•Deciphering toxicity mechanism of indoxacarb in zebrafish by spatial metabolomics.•Reduced liver detoxification ability lead to high exposure toxicity of indoxacarb.•This study provides new insights into exposure risks of insecticides and zebrafish.